Brentuximab vedotin: clinical updates and practical guidance - Yi, Jun Ho (Blood Res, 2017)
Brentuximab vedotin (BV), a potent antibody-drug conjugate, targets the CD30 antigen. Owing to the remarkable efficacy shown in CD30-positive lymphomas, such as Hodgkin's lymphoma and systemic anaplastic large-cell lymphoma, BV was granted accelerated approval in 2011 by the US Food and Drug Administration. Thereafter, many large-scale trials in various situations have been performed, which led to extensions of the original indication. The aim of this review was to describe the latest updates on clinical trials of BV and the in-practice guidance for the use of BV.